Classification of Healthcare Robots - Huang Rong (Switzerland, 2022)
With the advancement of artificial intelligence, robots have entered the healthcare field and provided various intelligent services. Compared to the growing number of use cases for healthcare robots, conceptual, and theoretical research on healthcare robots is still in its infancy. There is a need to explore how healthcare robots play different roles in society with the improvement of AI technology. To fill in this research gap, we provide a conceptualization of healthcare robots and a summary of main categories of healthcare robots in previous research. This study provides a classification of healthcare robots according to their service roles and discusses their differences in different dimensions, including appearance, presence, AI and automation ability, and social ability. Finally, we propose future research directions based on the discussion to provide insights into the conceptualization of healthcare robots. This study contributes to IS literature by providing a comprehensive knowledge base for further theory-building processes of AI-based healthcare robots and providing design guidance to robotic designers in specific healthcare fields.
Well-Being in the Information Society: When the Mind Breaks: 9th International Conference, WIS 2022, Turku, Finland, August 25–26, 2022, Proceedings